The Left Atrial Function as a Marker for the Severity of Heart Failure with Preserved Ejection Fraction - Sun, Mingxue; Shui, Zhiyuan; Wang, Yunzhi; Gao, Yiqun; Liang, Shunji; Wang, Yiran; Yu, Qin; Liu, Li (Cardiology and Cardiovascular Medicine, 2021)
Background: Heart failure with preserved ejection fraction (HFpEF) is a complex syndrome characterized by heart failure symptoms and signs, but normal or near-normal left ventricular ejection fraction (LV-EF). There are objective evidences of left ventricular systolic/diastolic dysfunctions and alteration of left atrial (LA) structure and functions. However, limited data are available on the association of LA functions with the severity of HFpEF. Methods: We assessed and analyzed LA/LV structure and functions in 61 patients with HFpEF with 2D echocardiography and two-dimensional speckle tracking echocardiographic technology (2D-STE). LA triphasic functions in subgroups with different classification of cardiac functions (NYHA II – IV) were compared. The correlation analysis of LA triphasic functions with LV systolic/diastolic functions was made with Pearson test. Results: Patients with HFpEF had impaired LV systolic/diastolic functions, and impaired LA triphasic functions compared with control subjects. LA global longitudinal strain (LA-GLS) and the left atrial systolic strain rate (LA-mSRs, reflecting LA reservoir function) were positively correlated with global LV longitudinal strain (LV-GLS) and E/e’; the longitudinal strain rate of the left atrium at the early diastole (LA-mSRe, reflecting LA conduit function) and the longitudinal strain rate of the left atrium at the late diastole (LA-mSRa, reflecting LA pump function) were inversely correlated with the LV-GLS and E/e’. The LA function is closely related with the NYHA classification in patients with HFpEF. Conclusion: LA phasic functions were significantly impaired in patients with HFpEF. It can be used as a marker for scaling the severity of HFpEF.